Workplace integration: Key considerations for internationally educated nurses and employers - Zubeida Ramji; Josephine Etowa (Administrative Sciences, 2018)
Integration of internationally educated nurses (IENs) in the workplace over the long term, has not been a clear focus in nursing. The role of the employer organization in facilitating workplace integration for IENs has also not been emphasized in research. The overall aim of this paper is to highlight findings from an instrumental qualitative case study research informed by critical social theory, which examined workplace integration of IENs. The study explored what is meant by 'integration' and how the employer organizational context affects workplace integration of IENs. A purposeful sample of twenty-eight participants was involved. The participants included: stakeholders from various vantage points within the case organization as well as IENs from diverse backgrounds who were beyond the process of transitioning into the Canadian workplace-they had worked in Canada for an average of eleven years. Four methods of data collection were used: semi-structured interviews; socio-demographic survey; review of documents; and focus group discussions (FGDs). Thematic analysis methods guided the within subcase analysis first, followed by an across subcase analysis. FGDs were used as a platform for member-checking to establish the credibility of study findings. The resulting definition and conceptual framework point to workplace integration of IENs as a two-way process requiring efforts on the part of the IENs as well as the employer organization. This paper elaborates on selected themes of how beyond transition, workplace integration entails IENs progressing on their leadership journey, while persevering to overcome challenges. Organizational factors such as workforce diversity, leadership commitment to equity and engagement with the broader community serve as critical enablers and the importance of workplaces striving to avoid common pitfalls in addressing the priority of IEN integration are also discussed. This paper concludes with implications and key considerations for workplace integration of IENs.
Keywords: 350; workplace integration; internationally educated nurses; conceptual framework; key considerations; employers